Visualizing multi-faceted functional decomposition of protein interaction networks (FACETS) - Chen, Mengxuan (2015)
Through the studies of the technical background of FACETS, FACETS Viewer was proposed in order to provide a user interface (UI) to visualize the protein interaction network. The key requirements of the software have been clearly stated, which requires re-designing user experience (UX). The visualization schemes were introduced accordingly. Not only were the UI components and layout considered, but the coloring methodology was also taken into account. In order to further implement the software, architectural design has been finalized and implementation details have been clarified, including the use of Gephi Toolkit package and Java Swing widget toolkit. Moreover, series of experiments were conducted across different network files to measure the performance of FACETS Viewer with different rendering configurations. Besides the technical details, a walkthrough for the software demonstrates an easy-to-follow workflow and its user-friendly interface. Finally, based on the experimental results, conclusions were given to summarize the project and recommendations were provided to suggest possible future improvement.